Relationship between mechanical properties of vitex doniana, a lesser known species and implications for utilization (2013)
Relationship between the mechanical properties of Vitex doniana, a lesser known wood species was investigated towards determining its potentials for utilization. Four trees obtained from the free area of Olokemeji Forest Reserve, Ogun State, Nigeria were sampled at butt (50cm above the ground) and at 10%, 30%, 50%, 70% and 90% of merchantable height (MH) The samples were also partitioned into corewood, middlewood and outerwood. Impact Bending (IMB), Modulus of Rupture (MOR), Modulus of Elasticity (MOE) and Maximum Compressive Strength Parallel to Grain (MCS//) were determined. Relationship between the mechanical properties was determined using regression equation. Results showed that Mean IMB, MOR, MOE and MCSS// were 0.69m, 85.4 N/mm2, 6380N/mm2 and 40.8N/mm2 respectively. The best relationship existed between IMB and MCS// (R2 = 0.75) followed by between MOR and MOE (R2 =0.71) while the least relationship (R2 = 0.43) existed between MOR and MCS//.